Illegal products and the question of consumer redress - Borna, Shaheen (Journal of business ethics, 1989)
Despite the enormous size of the illicit market in the United States, there is a paucity of research concerning the rights of consumers of illegal products. In this article it is argued that the illicit nature of a transaction should not deny consumers the right to safety and redress. Recognition of these rights is not only in line with the public policy goal, i.e., protecting public interests, but it can also serve as a deterrent factor for the sales of illegal products.